OPTIMAL CAPITAL STRUCTURE ANALYSIS OF PT GARUDA INDONESIA TBK. - Bisma Abdillah, Muhammad
PT Garuda Indonesia Tbk. is a well-known Indonesian national airline and has several subsidiaries such as PT Aero Wisata, PT Sabre Travel Network Indonesia, PT GMFAA, PT Citilink Indonesia, PT ASYST, PT Gapura Angkasa, and Garuda Indonesia Holiday France. As of April 2020, the world has been shaken into a critical condition because of Coronavirus pandemic and one of the most affected of this phenomenon is the airline industry, including PT Garuda Indonesia Tbk. Furthermore, most of the airline companies has lost many passengers due to the traveling restriction from the government to avoid disease transmission. Since then, PT Garuda Indonesia Tbk. should stop some flights to a certain domestic areas and foreign countries and also reduce the amount of passenger up to 50% and do a medical check for all passengers in every flight. Even more, In June 3, 2020, PT Garuda Indonesia is required to pay a maturing debt of USD 500 million to global sukuk limited and the government plans to provide a loan of IDR 8.5 trillion or as much as USD 600 million at an exchange rate of IDR 14,000 as of assumed exchange rate in 2020. Considering the debt that will be provided by the Indonesian Government, PT Garuda Indonesia Tbk. should take into consideration about the capital structure it will be if the company accept the loan. However, this decision is still being discussed by shareholders. Considering the recent condition of restriction of flights, reduced amount of passenger, and an increased cost of medical check, the author do a research into this company to determine what company action will PT Garuda Indonesia Tbk. should take. In order to decide whether the company accept the loan or not, the author analyses the current weighted average cost of capital of PT Garuda Indonesia Tbk. and searches the optimal capital structure so as to compare the debt and equity proportion of the current and the optimal condition of them. Seeing the line of business and volatility of earnings of PT Garuda Indonesia Tbk., the author takes a very conservative approach and therefore uses all the interest-bearing short-term and long-term debt and the market value of equity to realize the optimal capital structure it should have to determine what the best alternative financing strategy the company had to take. Therefore, to realize the plan, the company must be able to make the right proportion of loan calculations that have the lowest rate of return for investors, by calculating the optimal capital structure using the weighted average cost of capital (WACC) method. PT Garuda Indonesia Tbk. currently has 76% debt and 24% equity, where the cost of capital is 9.06% and through the WACC analysis, the authors have found that the optimal capital structure that PT Garuda Indonesia Tbk. must have to finance the maturing debt so that the value of the company at maximum, and should consist of USD 1,583,506,477 debt and USD 1,404,241,592 equity, which is 53% of debt and 47% of equity